2008
DOI: 10.1128/jvi.00902-08
|View full text |Cite
|
Sign up to set email alerts
|

E6 Proteins from Multiple Human Betapapillomavirus Types Degrade Bak and Protect Keratinocytes from Apoptosis after UVB Irradiation

Abstract: Human papillomavirus (HPV) types from the beta genus (beta-HPVs) have been implicated in the development of skin cancer. A potentially important aspect of their carcinogenic role is the ability of the E6 protein to degrade the proapoptotic family member Bak, which gives cells the ability to survive UV damage. However, it is unknown if the ability to degrade Bak is limited to certain beta-HPV types or whether E6 expression in keratinocytes affects other proteins important for apoptosis signaling. We tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
158
4
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 46 publications
4
158
4
4
Order By: Relevance
“…The main risk factors for cutaneous SCC are prolonged sun exposure and pigmentation grade of the skin. Interestingly, several studies have revealed diverse interactions of persisting betapapillomaviruses and UV irradiation, which may be relevant to the multi-step process of skin carcinogenesis (AkgĂŒl et al, 2005;Giampieri & Storey, 2004;Jackson & Storey, 2000;Jackson et al, 2002;Underbrink et al, 2008). We therefore evaluated the synergistic effects of UV light in transgenic animals.…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factors for cutaneous SCC are prolonged sun exposure and pigmentation grade of the skin. Interestingly, several studies have revealed diverse interactions of persisting betapapillomaviruses and UV irradiation, which may be relevant to the multi-step process of skin carcinogenesis (AkgĂŒl et al, 2005;Giampieri & Storey, 2004;Jackson & Storey, 2000;Jackson et al, 2002;Underbrink et al, 2008). We therefore evaluated the synergistic effects of UV light in transgenic animals.…”
Section: Introductionmentioning
confidence: 99%
“…the intrinsic pathway, which triggers sensing apoptotic signals that arise within the cell (DNA damage, oxidative stress) [54]. The lr/hrE6 oncoproteins block intrinsic apoptotic signaling interacting with Bak, inducing its proteasomal-dependent degradation [55], or using a mechanism depending or not on E6AP and E3 ubiquitin ligases [56].…”
Section: E6 Hpvmentioning
confidence: 99%
“…30 Additionally, b-PV E6 targets the pro-apoptotic protein Bak for degradation. 31,32 These effects, usually combined with mechanisms that delay DNA repair (like abrogation of ATR activity 33 ) or impairment of the telomere/ telomerase system 34 may explain b-PV contribution to skin carcinogenesis by favoring the accumulation of UV damaged cells. The oncogenic potential of b-PV has also been shown in in vivo transgenic models which develop SCC in response to b-PV gene expression, either spontaneously or after UV irradiation.…”
Section: Introductionmentioning
confidence: 99%